Long‑term climatic water availability trends and variability across the African continent - Onyutha, Charles (Theoretical and Applied Climatology, 2021)
This study analyzed trends and variability in climatic water availability (CWA) across the African continent using monthly precipitation and potential evapotranspiration (PET) over the period 1901–2015. Climatic water availability was characterized in terms of precipitation minus PET totals. Predictability of the variation in CWA was tested using climate indices. Large positive values of the CWA (or few drought incidents) were confined to areas (such as sub-region along the Gulf of Guinea, the western part of the equatorial region, and the Ethiopian Highlands) that receive large amounts of precipitation. Drought incidence in these areas was generally low and characterized by severity in the range 0–44% indicating moderate to extreme wetness. Areas which experienced increasing CWA or wetting trends were confined within the Tropics. These wetting trends were mostly insignificant (p > 0.05). Drying trends (or decreasing CWA) occurred mainly in areas outside the Tropics. These drying trends (especially in the CWA of the months from April to September) were mainly significant (p < 0.05) over the Sahara desert. CWA variability in the southern and eastern parts of Africa was negatively and positively correlated with Niño 3, respectively. Variability of the East African CWA was also positively correlated with the Indian Ocean Dipole (IOD). CWA variability in West Africa (or Sahel) was negatively correlated with Niño 3. Variability of West African CWA was also linked to changes in the sea surface temperature over the Atlantic Ocean. Based on multiple linear regression, predictability of variation in CWA using combinations of climate indices varied across regions and among time scales. For instance, using combination of IOD and Niño 3 as predictors, up to about 40% and less than 10% of the total variance in CWA across East Africa and area north of the Sahel belt could be explained, respectively.
Keywords: Climatic water; African continent